2013
DOI: 10.1007/s11065-013-9234-5
|View full text |Cite
|
Sign up to set email alerts
|

Atypicalities in Cortical Structure, Handedness, and Functional Lateralization for Language in Autism Spectrum Disorders

Abstract: Language is typically a highly lateralized function, with atypically reduced or reversed lateralization linked to language impairments. Given the diagnostic and prognostic role of impaired language for autism spectrum disorders (ASDs), this paper reviews the growing body of literature that examines patterns of lateralization in individuals with ASDs. Including research from structural and functional imaging paradigms, and behavioral evidence from investigations of handedness, the review confirms that atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 99 publications
10
114
2
Order By: Relevance
“…Research from the human literature suggests that people with pervasive developmental disorders (e.g., Autism Spectrum Disorder), veer more towards left-than right-handedness (for review, Lindell & Hudry, 2013). There is a tendency for such individuals to be relatively 'rigid' in their outlook, finding it challenging to overlook minute details.…”
Section: Discussionmentioning
confidence: 99%
“…Research from the human literature suggests that people with pervasive developmental disorders (e.g., Autism Spectrum Disorder), veer more towards left-than right-handedness (for review, Lindell & Hudry, 2013). There is a tendency for such individuals to be relatively 'rigid' in their outlook, finding it challenging to overlook minute details.…”
Section: Discussionmentioning
confidence: 99%
“…While mixed-handedness makes up approximately 3-4% of the general population [e.g. 42], populations with ASD reveal mixed-handedness at proportions of between 17% and 47% [for a review see 43]. However, it has been reported that children with ASD who possess either left or right hand dominance, generally tend to have stronger language capabilities, compared with mixed-handed children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…The most documented risk is for autism 24 . With relevance to the present study, theories have linked the communication difficulties in autism with atypical lateralisation 25 and left hemisphere dysfunction 26 . In addition, the 47,XXX and 47,XXY karyotypes have been explored as genetic models for schizophrenia 5 , although an increased risk for schizophrenia is not well established 27 .…”
Section: Cc-by-nc-ndmentioning
confidence: 84%